New insights into the role of Klotho in inflammation and fibrosis: molecular and cellular mechanisms - Zhao, Xinyue; Han, Donghe; Zhao, Chun; Yang, Fengfan; Wang, Zhimei; Gao, Yujiao; Jin, Meihua; Tao, Ran (Frontiers in Immunology, 2024)
As the body’s defense mechanism against damage and infection, the inflammatory response is a pathological process that involves a range of inflammatory cells and cytokines. A healthy inflammatory response helps the body repair by eliminating dangerous irritants. However, tissue fibrosis can result from an overly intense or protracted inflammatory response. The anti-aging gene Klotho suppresses oxidation, delays aging, and fosters development of various organs. Numerous investigations conducted in the last few years have discovered that Klotho expression is changed in a variety of clinical diseases and is strongly linked to the course and outcome of a disease. Klotho functions as a co-receptor for FGF and as a humoral factor that mediates intracellular signaling pathways such as transforming growth factor β (TGF-β), toll-like receptors (TLRs), nuclear factor-kappaB (NF-κB), renin -angiotensin system (RAS), and mitogen-activated protein kinase (MAPK). It also interferes with the phenotype and function of inflammatory cells, such as monocytes, macrophages, T cells, and B cells. Additionally, it regulates the production of inflammatory factors. This article aims to examine Klotho’s scientific advances in terms of tissue fibrosis and the inflammatory response in order to provide novel therapy concepts for fibrotic and inflammatory disorders.